2010
DOI: 10.1007/s11262-010-0456-9
|View full text |Cite
|
Sign up to set email alerts
|

Cocksfoot mottle sobemovirus coat protein contains two nuclear localization signals

Abstract: Cocksfoot mottle virus (CfMV) coat protein (CP) localization was studied in plant and mammalian cells. Fusion of the full-length CP with enhanced green fluorescent protein (EGFP) localized to the cell nucleus whereas similar constructs lacking the first 33 N-terminal amino acids of CP localized to the cytoplasm. CP and EGFP fusions containing mutations in the arginine-rich motif of CP localized to the cytoplasm and to the nucleus in plant cells indicating the involvement of the motif in nuclear localization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Results obtained here, with viruses containing the same mutations in CP, demonstrate that these mutations have no deleterious effect on virus cell-to-cell and systemic movement as well as on mechanical transmission in oats. The majority of CP-EGFP fusion protein localises to the cell nucleus when expressed independently from the rest of the virus genome [13]. Here we observed that when CP-EGFP was expressed together with the rest of the viral proteins, the fluorescence did not accumulate in the nucleus, but remained evenly distributed between cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Results obtained here, with viruses containing the same mutations in CP, demonstrate that these mutations have no deleterious effect on virus cell-to-cell and systemic movement as well as on mechanical transmission in oats. The majority of CP-EGFP fusion protein localises to the cell nucleus when expressed independently from the rest of the virus genome [13]. Here we observed that when CP-EGFP was expressed together with the rest of the viral proteins, the fluorescence did not accumulate in the nucleus, but remained evenly distributed between cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 71%
“…The CP of mutants R3L and R5X localises to cytoplasm and nucleus whereas the wt CP localises almost exclusively to the nucleus [13]. Results obtained here, with viruses containing the same mutations in CP, demonstrate that these mutations have no deleterious effect on virus cell-to-cell and systemic movement as well as on mechanical transmission in oats.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Studies on RNA plant viruses have reported the presence of virus-encoded proteins in the nucleus: in the Cucumber mosaic virus (CMV), the silencing suppressor protein 2b displayed nuclear localization (36); the Tombusvirus p19 is also translocated by plant ALY proteins to the nucleus (13). In other RNA plant virus systems, such as sobemovirus, umbravirus, potyvirus, luteoviruses, and the Satellite panicum mosaic virus (SPMV), the CP itself is localized to the nucleus (20,30,47,49,56). To date, the function of nucleolar localization has been shown in only two systems: in umbraviruses, ORF3 localization to the nucleolus was described as being necessary for long-distance virus spread (31).…”
Section: Discussionmentioning
confidence: 99%
“…Grapevine rupestris stem pitting-associated virus CP has a signal that brings it into the plant cell nucleus . Similarly, Cocksfoot mottle virus (CfMV) CP has nuclear localization signals (Olspert et al 2010). The role of these localizations is unclear.…”
Section: Movement and Coat Proteinsmentioning
confidence: 99%